Interdependency Between Autophagy and Synaptic Vesicle Trafficking: Implications for Dopamine Release - Limanaqi, Fiona; Biagioni, Francesca; Gambardella, Stefano; Ryskalin, Larisa; Fornai, Francesco (Frontiers in Molecular Neuroscience, 2018)
Autophagy and the Ubiquitin Proteasome are the main clearing systems of eukaryotic cells, in that being ultimately involved in degrading damaged and potentially harmful cytoplasmic substrates. Emerging evidence implicates that, in addition to their classic catalytic function in the cytosol, autophagy and the proteasome act as modulators of neurotransmission, inasmuch as they orchestrate degradation and turnover of synaptic vesicles and related proteins. These findings are now defining a novel synaptic scenario, where clearing systems and secretory pathways may be considered as a single system, which senses alterations in quality and distribution (in time, amount and place) of both synaptic proteins and neurotransmitters. In line with this, in the present manuscript we focus on evidence showing that, a dysregulation of secretory and trafficking pathways is quite constant in the presence of an impairment of autophagy-lysosomal machinery, which eventually precipitates synaptic dysfunction. Such a dual effect appears not to be just incidental but it rather represents the natural evolution of archaic cell compartments. While discussing these issues, we pose a special emphasis on the role of autophagy upon dopamine neurotransmission, which is early affected in several neurological and psychiatric disorders. In detail, we discuss how autophagy is engaged not only in removing potentially dangerous proteins, which can interfere with the mechanisms of dopamine release, but also the fate of synaptic dopamine vesicles thus surveilling dopamine neurotransmission. These concepts contribute to shed light on early mechanisms underlying intersection of autophagy with dopamine-related synaptic disorders.